Description of the first juvenile of Aegla franca Schmitt, 1942 (Crustacea, Decapoda, Aeglidae) - Francisco, Débora A.; Bueno, Sérgio L.s.; Kihara, Terue C. (Zootaxa, 2007)
The post-embryonic development in Aegla franca is epimorphic, in which the hatching form is a juvenile that very much resembles the adults in general morphology. Newly-hatched juveniles were obtained under laboratory conditions from ovigerous females bearing eggs at late embryonic stage, and collected from the wild. Upon hatching, some juvenile specimens were cleared, stained, dissected and prepared for light microscopy on semi-permanent slides and each appendage was described in detail and illustrated accordingly. Some specimens were also prepared for scanning electron microscopy to obtain detailed information concerning setal morphology and ultrastructure of some cephalothoracic appendages. Comparison of the present results to previous descriptions of the first juvenile of other aeglid species show some interesting features observed only in Aegla franca. These features include the presence of pores on the first and second pairs of antennae; the rudimentary condition of the mandible and the long setae with a subterminal pore and scaly outgrowth distally on the basal bilobed endite of the maxilla.